Essential role of connective tissue growth factor (CTGF) in transforming growth factor-β1 (TGF-β1)-induced myofibroblast transdifferentiation from Graves’ orbital fibroblasts - Chieh-Chih Tsai (Nature Portfolio, 2018)
Abstract Connective tissue growth factor (CTGF) associated with transforming growth factor-β (TGF-β) play a pivotal role in the pathophysiology of many fibrotic disorders. However, it is not clear whether this interaction also takes place in GO. In this study, we investigated the role of CTGF in TGF-β-induced extracellular matrix production and myofibroblast transdifferentiation in Graves’ orbital fibroblasts. By Western blot analysis, we demonstrated that TGF-β1 induced the expression of CTGF, fibronectin, and alpha-smooth muscle actin (α-SMA) in Graves’ orbital fibroblasts. In addition, the protein levels of fibronectin and α-SMA in Graves’ orbital fibroblasts were also increased after treatment with a recombinant human protein CTGF (rhCTGF). Moreover, we transfected the orbital fibroblasts with a small hairpin RNA of CTGF gene (shCTGF) to knockdown the expression levels of CTGF, which showed that knockdown of CTGF significantly diminished TGF-β1-induced expression of CTGF, fibronectin and α-SMA proteins in Graves’ orbital fibroblasts. Furthermore, the addition of rhCTGF to the shCTGF-transfected orbital fibroblasts could restore TGF-β1-induced expression of fibronectin and α-SMA proteins. Our findings demonstrate that CTGF is an essential downstream mediator for TGF-β1-induced extracellular matrix production and myofibroblast transdifferentiation in Graves’ orbital fibroblasts and thus may provide with a potential therapeutic target for treatment of GO.